Behavioural impact on internet usage and internet advertisements preference on young individuals. (2017) - Shanthi, P.; Thiyagarajan, S.
Advertisements over internet can be seen as a boon or bane for the internet users especially to youth who are the major contributors to internet usage. Any advertisement, if noticed, can lead to a particular behaviour or action. And internet advertisements are no exceptions. Most reviews with respect to internet advertisements indicate that it is disturbing for the genuine users and distracting to the youth. The five types of advertisements considered in this study are: social advertisements, sexy advertisements, celebrity advertisements, personal advertisements and promotional advertisements. This paper thus focuses on the behaviour of the youth with respect to the viewing of advertisements. The sample size of the study was 700 with schools and universities in Pondicherry and Chennai. The instrument used for data collection was a questionnaire. A SEM model was developed based on the responses collected to study the influence of advertisements on the positive and negative behaviours. Findings and suggestions were made based on the results. This study stands unique in the fact that there are no direct empirical studies based on the influence of positive and negative behaviours of youth on internet advertisements especially in the regions (Pondicherry and Chennai) considered in the study.